A novel sieve plate hole pattern: effect on gas hold-up and flow regimes in a bubble column. Issue 12 (1st December 2020) - Sánchez-Morán, Héctor; Terleira, Marina; Díaz, M. Elena; Montes, Francisco J.
Abstract: The effect of an innovative sieve plate orifice layout on the hydrodynamics of a cylindrical bubble column is investigated. The classical triangular layout is compared with a novel spiraled layout, using the same number and diameter of orifices. The experiments include two different column aspect ratios and two liquid phases of different coalescing nature. According to the holdup data, if the spiraled layout is used, the flow regimes evolve from a pseudo-homogeneous regime to a heterogeneous regime going through a transition regime, as the superficial gas velocity increases. When the triangular layout is used, the homogeneous regime is not detected and pure heterogeneous regime is obtained at all superficial gas velocities. When using the spiraled layout, the gas retention increases, resulting 24% higher in the homogeneous regime and 13% higher in the heterogeneous regime with respect to the gas retention obtained with the triangular layout. If bubble coalescence is modified by the addition of NaCl, the holdup increases for both layouts, but to a lower extent in the spiraled layout (10%) compared to the triangular layout (24%). The reason behind the reduction of coalescence and higher gas holdup values is the ability of the spiraled layout to produce bubbles that do not interact with each other during a longer path along the column.